PERAN GURU PPKn DALAM MENGEMBANGKAN KECERDASAN MORAL SISWA DI SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO TAHUN PELAJARAN 2022/2023 - Febrius Laia (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
This research is motivated by the lack of moral intellegence of students; for example talking to each other when the teacher explains the learning material, or they don't listen to the teacher when being advised. To address these problems, researchers conducted research of the Role of Civics Teachers in Developing Students' Moral Intelligence at SMP Negeri 1 Luahagundre Maniamolo. This study aims to find out the Role of Civics Teachers in Developing Students' Moral Intelligence at SMP Negeri 1 Luahagundre Maniamolo. The approach used in this research is a qualitative approach with a descriptive research type. The source of the data in this study is Civics teachers and students, totaling 10 people. Data collection techniques in this study were carried out by (1) observation, (2) interviews, (3) documentation studies. The data analysis technique in this study was carried out through three series of activities (1) data reduction (2) data model (3) withdrawal of verification/conclution. The teacher's suggestions should be able to carry out their role properly so that students are able to follow the directions given. The teacher should be a good role model able to show attitudes and behavior that are in accordance with everyday life so that students have good moral intelligence.